Complementarity and Evolution of Contractual Provisions: An Empirical Study of IT Services Contracts - Argyres, Nicholas S.; Bercovitz, Janet; Mayer, Kyle J. (Organization Science, 2007)
An increasing volume of business activity appears to be occurring via alliances or other interfirm arrangements in which complex contracts are featured, yet there has been relatively little study of contract design in the strategy or management literatures. The economics literature on contracting has been extensive, but it has been less concerned with learning and evolution—phenomena in which strategy and organization scholars are deeply interested. In this paper, we investigate the relationship between two types of contractual provisions that are important in high-technology contracts, or contracts for which environmental uncertainty or technological complexity are significant, namely, contingency planning and task description. Previous research suggests that contracts can vary significantly in the degree of detail with which such key provisions are written, and that they are each subject to learning. In this paper, we find evidence from a sample of 386 contracts that contingency planning and task description behave as complements in contractual design. We argue that this complementarity reflects patterns of learning to contract. We also find that repeated exchange between two firms leads to greater effort at contingency planning in subsequent contracts, a finding that is also consistent with learning effects, but not with frequently made claims that contracts and trust are substitutes.